Optimalisasi Pengelolaan Usaha Bumdes Loh Jinawi Dalam Meningkatkan Kesejahteraan Ekonomi Masyarakat Desa Berkelanjutan di Purbalingga - Anandhiya Intan Prabandari; Rinny Apriliany Zakaria; Febyana Putri Komalasari; Dian Isnawati; Sausan Nuhaa Maisaroh; Laurensia Claudia Pratamo (Lembaga Pengembangan Kinerja Dosen, 2025)
Village-Owned Enterprises (BUMDes) are business units that are jointly owned and managed by the village government and the local community. The establishment of BUMDES aims to exploit economic potential and improve the welfare of village communities. One of the BUMDes highlighted in this study is BUMDes Loh Jinawi which is located in Tunjungmuli Village, Karangmoncol District, Purbalingga Regency. In its development, Tunjungmuli Village is still faced with geographical challenges and inadequate infrastructure. BUMDes Loh Jinawi manages four main business units, namely Pertashop, Pamsimas, Markets, and innovations in the agricultural sector so that they can meet the basic needs of the community. Pertashop provides access to fuel, Pamsimas ensures clean water supply, Markets support local trade, and agricultural units increase food security and farmer incomes through sustainable practices. These initiatives have significantly improved the quality of life and economic opportunities for local residents, especially farmer groups. Through participatory management and community involvement, BUMDes Loh Jinawi has fostered a sense of belonging among residents while overcoming socio-economic challenges. The authors contributed by facilitating observations, workshops and mentoring to improve BUMDes operations. In a series of community service activities, it was found that optimizing the management of BUMDes Loh Jinawi can be done in two ways, namely assisting with management practices to increase access to basic services and empowering the surrounding community economically and socially. This study provides a replicable model for sustainable rural development.